EEFECT OF BRAND PACKAGING POSITIONING STRATEGY ON CUSTOMERS’ BEHAVIOURAL INTENTIONS TOWARDS FOOD AND BEVERAGE PRODUCTS: EVIDENCE FROM NIGERIA - Dr Lawrence Amadi (Scholar Express Journal, 2022)
The study examined the effect of brand packaging positioning strategy on customers’ behavioural intentions in the context of repeat purchase towards food and beverage brands in Rivers State, Nigeria.The study adopted descriptive research design. Data were drawn through a well-structured questionnaire from 384 customers of food and beverage manufacturing SMEs in Rivers State. The hypothesized relationship was tested with simple regression analysis with the aid of SPSS (version 21.0). The statistical results showed that brand packaging positioning strategy studied was critical in determining the outcome of customers’ behavioural intentions in the context of repeat purchase towards food and beverage brands in Rivers State. It was found to have significant predictive capabilities on customers’ behavioural intentions. In conclusion, brand packaging positioning strategies had significant statistical influence on customers’ behavioural intentions in the context of repeat purchase towards food and beverage brands in Rivers State. Precisely, 63.8%, changes in customers’ behavioural intentions were significantly predicted by brand packaging. Therefore, this study recommended that food and beverage SMEs should develop packaging strategy that is capable of differentiating their brands from competing brands in the marketplace and also meet customers’ expectations
Keywords: Brand Packaging Positioning Strategy; Repeat Purchase; SMEs; Food and Beverage Brands